Caleg, Kamera, dan Citra Diri: Evaluasi Personal Branding Politik di Media Digital (Lembaga Pengembangan Kinerja Dosen, 2025)
The digital era has revolutionized the way legislative candidates (caleg) build their self-image and reach voters. This study aims to evaluate the personal branding strategies used by candidates for the Indonesian House of Representatives (DPR RI) through digital media, especially visual social media such as Instagram, TikTok, and YouTube. Using a qualitative approach through content analysis and semi-structured interviews with political communication experts and legislative candidate campaign teams, this study identified that the effectiveness of personal branding is largely determined by three main elements: authenticity, narrative consistency, and interactivity. These three elements have been proven to be able to increase emotional connectivity between legislative candidates and digital voters, especially the younger generation. However, there was also an imbalance between the digital image built and the public's perception in the field, which can reduce the level of trust in the political representation displayed. The results of this study provide an important contribution to understanding the dynamics of digital political communication and strengthening more ethical, transparent, and participatory campaign practices in Indonesian electoral democracy.